Efektifitas Pembelajaran Guided Teaching dengan E-Learning untuk Meningkatkan Kemampuan Komunikasi Matematik Mahasiswa - Kusuma, Adi Candra; Afriliana, Ida (Desimal: Jurnal Matematika, 2018)
To many abstract concepts in mathematics learning make students think mathematics is difficult. The purpose of this research is to obtain the effectiveness of Guided Teaching learning with E-learning to improve students 'mathematical communication skills by 1) students' mathematical communication skills who are given Guided Teaching learning with E-Learning achieve minimal mastery of both individual and classical learning, 2 ) students' mathematical communication skills are given Guided Teaching learning treatment with E-Learning better than expository learning, and 3) an increase in mathematical communication skills of students who are given Guided Teaching learning treatment with E-Learning better than expository learning. The method used in the experiment (quantitative). Data collection methods using observation, interviews, and tests about students' mathematical communication skills. Data analysis uses the completeness test, proportion test, comparative test, and N-Gain test. The results of this study obtain the effectiveness of guided teaching-learning with e-learning as follows (1) individual completeness meets KKM (68), (2) classical completeness by 75% with the proportion of students already getting 68 grades has exceeded 75%; (3) students 'mathematical communication skills of Guided Teaching learning with e-learning by 80.75 higher than expository learning by 69.50 (4) an increase in students' mathematical communication skills of 0.407 medium categories and the difference in the increase in mathematical communication skills of students who were given treatment guided teaching-learning with e-learning is greater than Expository learning.